Between Worlds : Forging an African Mission Church in Southern Africa - Switzer, Les, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2025)
Between Worlds expands beyond the focus of the previous volume-the British colony of Natal-to the more challenging framework of the American Zulu Mission and its Congregational churches in southeastern Africa between the 1880s and 1920s. This study rejects arguments by many critical scholars, who see Western missionaries at best as adjuncts of the colonial project, imposing an understanding of Western Christianity that inevitably clashes with alien and resistant African cultures. The mission-church relationship in this era also changes dramatically especially in urban environments. The church in South Africa becomes the dominant partner from the 1880s and by 1900 the mission has become an adjunct of the church-an understanding with far-reaching consequences elsewhere in the subcontinent.